Functional role of branched chain amino acids in poultry: a review - Woo Kyun Kim; Amit Kumar Singh; Jinquan Wang; Todd Applegate (Poultry Science, 2022)
ABSTRACT: This review provides insight into the effects of the branched-chain amino acids (BCAA: leucine, isoleucine, and valine) on the growth, production performance, immunity, and intestinal health of poultry. Besides providing nitrogen substrates and carbon framework for energy homeostasis and transamination, BCAA also function as signaling molecules in the regulation of glucose, lipid, and protein synthesis via protein kinase B and as a mechanistic target of the rapamycin (AKT-mTOR) signaling pathway that is important for muscle accretion. The level of leucine is generally high in cereals and an imbalance in the ratio among the 3 BCAA in a low protein diet would produce a negative effect on poultry growth performance. This occurs due to the structural similarity of the 3 BCAA, which leads to metabolic competition and interference with the enzymatic degradation pathway. Emerging evidence shows that the inclusion of BCAA is essential for the proper functioning of the innate and adaptive immune system and the maintenance of intestinal mucosal integrity. The recommended levels of BCAA for poultry are outlined by NRC (1994), but commercial broilers and laying hen breed standards also determine their own recommended levels. In this review, it has been noted that the requirement for BCAA is influenced by the diet type, breed, and age of the birds. Additionally, several studies focused on the effects of BCAA in low protein diets as a strategy to reduce nitrogen excretion. Notably, there is limited research on the inclusion ratio of BCAA in a supplemental form as compared to the ingredient-bound form which would affect the dynamics of utilization in different disease-challenged conditions, especially those affecting digesta passage ratio. In summary, this review encompasses the role of BCAA as functional AA and discusses their physiological effects on the productivity and health of poultry. The observations and interpretations of this review can guide future research to adjust the recommended levels of BCAA in feeding programs in the absence of subtherapeutic antibiotics in poultry.